Sustaining Odisha's legacy: Traditional rice cakes as cultural treasures - Panda, Taranisen; Dikshit, Nilamani; Mishra, Nirlipta; Rahimuddin, Shaik; Pradhan, Bikram; Mohanty, Raj Ballav (Ethnobotany Research and Applications, 2024)
Background: Food in India reflects the complex interplay of caste, class, and spirituality, creating a cultural tapestry that mirrors societal intricacies. This paper focuses on the indigenous knowledge held by women in Odisha's coastal regions, shedding light on the cultural richness surrounding rice cakes and emphasizing the need to preserve these culinary traditions in the face of modernization. Methods: To catalog rice cake varieties, we conducted a survey in the coastal districts of Odisha, India, covering three seasons. Data from one hundred and thirty-three female informants were gathered through semi-structured interviews, key informant discussions, and direct observations. Results: The study documented ten types of rice cakes, ranging from Arisa to Tala Pitha. These rice cakes highlighted a culinary fusion, blending rice with diverse plant and animal-based ingredients, including chenna, coconut (Cocos nucifera), groundnut (Arachis hypogea), ada (Zingiber officinale), among others. Notably, these rice cakes held profound socio-cultural significance—Manda for Kumar Purnima, Poda for Ratha Jatra, and Arisa for marriage ceremonies. All the documented Pithas’ were exclusively crafted at the household level, showcasing the expertise and culinary skills of the women in the coastal districts of Odisha. Conclusion: These traditional culinary delights, steeped in tradition, symbolize auspicious occasions, preserving the region's culinary heritage. Passed down through generations, the art of crafting these rice cakes strengthens intergenerational bonds and safeguards cultural traditions. Initiatives like "Food Festivals" play a crucial role in revitalizing indigenous cuisine, fostering awareness, and inspiring the youth to actively contribute to the preservation of their cultural identity. Keywords: Coastal Odisha, Indigenous knowledge, Ethnic food, Natural resources, Rice cake